UTBK-Based Higher Order Thinking Skills (HOTS) Test Instruments on Reaction Rate Topic - Minata, Zelen Surya; Agustina, Nur Indah; Ardianty, Annida Elfiana Citra; Rahayu, Sri; Muntholib (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
One of the efforts that can be support students in developing 21st century skills is to implement learning based on 21st century skills. In addition, another alternative that can be taken is to create, direct, and provide HOTS-based test instruments as an evaluation of learning. This study aims to develop multiple choice test instruments and essays to measure learners' Higher Order Thinking Skills (HOTS) on reaction rate materials. This research uses the Research and Development (R & D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The respondents in the study were 150 students of class XII MIPA one of the high schools who had received learning material on reaction rate. The results of the validity of the product contents show that the question instrument is 92.01% valid with an excellent category. The results of empirical validity show that as many as 20 items of multiple-choice questions and 8 items of essay questions are valid and have high reliability with Cronbach Alpha scores of multiple-choice questions of 0.723 and essay questions of 0.736. The difference between the question items from the two types of questions is categorized very well with 20 items of multiple-choice questions categorized as moderate, while in essay questions, 1 question is categorized as easy and 7 questions are categorized as moderate. Furthermore, the question instruments that have been developed can be used to measure the HOTS of students.